HUBUNGAN MANAJEMEN KONFLIK DENGAN KINERJA PERAWAT DI RUANGAN RAWAT INAP RSUD. DR. HASRI AINUN HABIBI PROVINSI GORONTALO - Rini Asnawati; Fahmi A. Lihu (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
This study aims at investigating the relationship of conflict management and professionalism performed by nurses in RSUD Ainun Habibie. It uses Quantitative Descriptive design and cross sectional study approach. Population is 51 nurses who are taken through accidental sampling technique. The statistical testing used is spearman rank. The result shows that correlation value as 0.419 is higher than rHo 0.334 and p value as 0.015 is lower than α < 0.05; thus, Ho is rejected and Ha is accepted. The conclusion is conflict management influences positively to professionalism performed by nurses.